Student's works Neo Studio semester 03: 03. Tribe Pod / Nurul Shafinaz Jamel - Jamel, Nurul Shafinaz (Perpustakaan Tun Abdul Razak, UiTM Sarawak, 2024)
Sarawak’s most attractive features are their cultural diversity. The objective of the brief is to promote Sarawak culture by showing to the world, the uniqueness of the local ethnics. The Tribe Pod project is to promote an ethnic by showing the identity and the character of the tribe in different perspectives. The second project aims to create a Furnitecture which is furniture that is intended to accompany architecture. The tasks introduced the students to design an innovative chair based on the ethnics’ special characteristic to promote Sarawak’s local tribe’s culture and craft in modern and contemporary way. The final project is to design a hut for tourist to stay at the particular place for some time for 2 to 3 persons. The objective of the projecct aim to introduced student to implement the anthrometric and ergonomic and explore the multipurpose of the spaces to emphasize flexibility of the spaces.